Impact of neoadjuvant chemoradiotherapy followed by surgical resection on node-negative T3 and T4 non–small cell lung cancer - Daly, Benedict D.T.; Ebright, Michael I.; Walkey, Allan J.; Fernando, Hiran C.; Zaner, Ken S.; Morelli, Donna M.; Kachnic, Lisa A. (The Journal of thoracic and cardiovascular surgery, 2011)
This study examined the impact of neoadjuvant chemotherapy and concurrent high-dose radiation therapy on survival in patients with node-negative T3 and T4 non–small cell lung cancer. A total of 110 consecutive patients underwent surgical resection for invasive T3N0M0 (94 patients) and T4N0M0 (16 patients) non–small cell lung cancer between 1979 and 2008. Forty-seven patients received neoadjuvant chemotherapy and concurrent high-dose (5940 cGy) radiation therapy before resection (Chemo-RT group). Sixty-three patients underwent surgical resection without receiving induction chemoradiotherapy (Surg group), of whom 21 received neoadjuvant radiation, 19 received adjuvant radiation, 17 received surgery alone, 2 received adjuvant chemotherapy, 2 received adjuvant chemoradiotherapy, and 2 received brachytherapy. Survival of the Chemo-RT and Surg groups was compared using both crude and adjusted Cox proportional hazards models. The 5-year, 10-year, and median survivals were 61%, 50%, and 90 months, respectively, in the Chemo-RT group versus 22%, 14%, and 22 months, respectively, in the Surg group. Subjects in the Surg group had an increased risk of death (hazard ratio, 2.60; 95% confidence interval, 1.62–4.18; P = .0001) compared with the Chemo-RT group. After adjustment for potential confounding variables of age, sex, tumor size, tumor location, type of operation, and decade of care, subjects in the Surg group remained at increased risk of death (hazard ratio, 2.81; 95% confidence interval, 1.45–5.44, P = .002) compared with the Chemo-RT group. Aggressive treatment of node-negative invasive T3 and T4 NSCLC with induction chemoradiotherapy may significantly prolong survival. This approach should be evaluated in a prospective multicenter national trial.